Is Abandonment of Nonoperative Management of Hypertrophic Pyloric Stenosis Warranted? - Lukac, Marija; Antunovic, Sanja Sindjic; Vujovic, Dragana; Pavicevic, Polina; Jesic, Milos; Krstajic, Tamara; Petronic, Ivana; Nikolic, Dejan (European Journal of Pediatric Surgery, 2013)
Aim Evaluation of the effectiveness of oral atropine versus surgical therapy for hypertrophic pyloric stenosis (HPS).Methodology A total of 66 consecutive patients with HPS were treated at the University Children's Hospital between January 2006 and December 2011. The diagnosis was initially based on medical history and confirmed by ultrasonography (US). The patients were divided into two groups according to the treatment preferred by their parents. The conservatively treated group, consisting of 33 boys and 7 girls, mean age 22.25 days, was given water-soluble atropine sulfate therapy at an initial dose of 0.05 mg/kg/day divided into 8 single doses, and administered after stomach decompression, 20 minutes prior to feeding. If vomiting persisted, the daily dose was progressively increased up to 0.18 mg/kg. If vomiting did not stop and full oral feeding was not reestablished in a week, surgery was done. The second group of 26 patients, mean age 20.86 days, underwent an operative procedure, Ramstedt extramucosal pyloromyotomy after the initial resuscitation. US evaluation was performed on days 7, 14, and 21. The outcome of the treatment was tested by Yates modification of the χ2 test.Results In the group of patients treated with atropine sulfate, 10 (25%) failed to respond to therapy, therefore, 8 boys and 2 girls underwent surgical treatment between the fifth and seventh day following institution of therapy. The remaining patients who received atropine sulfate (75%) were discharged when vomiting ceased, between the sixth and eighth day. They continued to take oral medication for 4 to 6 weeks, and were followed up by an ultrasound examination. The operated patients were discharged between the third and fifth day after surgery. There was a significant statistical difference between the groups regarding the outcome at a significance level of p < 0.05 (Yates χ2 = 5.839), with no complications regardless of the treatment option. However, at the significance level of p < 0.01 (Yates χ2 = 7.661), these methods demonstrate a difference in favor of surgical treatment.Conclusion Further investigation of oral, intravenous or combined atropine sulfate treatment may clarify its position as an alternative to pyloromyotomy.
Keywords: hypertrophic pyloric stenosis; conservative treatment; atropine sulfate; pyloromyotomy